The two Charlies: the crime lives and double murder of Kansas City mobsters Binaggio and Gargotta - Hausner, Larry J. (Exposit, 2023)
""Charles Binaggio and his underboss, Charles Gargotta, rose through poverty in Missouri to eventually lead the Kansas City mob. In the 1930s and 40s, their control extended from local police and businessmen all the way to the White House. The two men died together in an unsolved 1950 double murder in downtown Kansas City. This work offers a unique take on the stories of the two Charlies, with first-hand accounts from those who worked for the gangsters as well as those who felt their wrath. In addition to their violence and corruption, it also reveals the two mobsters' private lives with their wives and children, and describes their inner political connections both within Kansas City and inside Harry S. Truman's administration."-Provided by publisher"--